The impact of improper promotion of sports lottery on the harm of purchasing sports lottery: an intermediary in a regulatory chain - Li, Gai; Li, Yang; Liu, Lian (Frontiers in Psychiatry, 2026)
IntroductionTo explore the relationship between the improper promotion of lottery games and the harm caused by lottery players' purchase of lottery tickets, as well as the chain mediating role of the compulsive tendency of lottery purchase addiction, bad lottery purchase behaviors, and responsible lottery purchase beliefs.MethodsA questionnaire survey was conducted on 600 lottery players, and the data were analyzed using SPSS 27.0 and the PROCESS plugin.Results(1) The improper promotion of sports betting is directly related to the harm caused by sports betting; (2) The improper promotion of sports betting is related to the harm through three indirect pathways: namely, through the compulsive tendency of gambling addiction, bad gambling behaviors, and the chain relationship between gambling addiction and bad gambling behaviors as mediating factors; (3) The belief of responsibility when purchasing lottery tickets played a moderating role in the impact of improper sports betting promotion on gambling addiction behavior, which could buffer the impact of improper sports betting promotion on gambling addiction behavior and the impact of problem gambling behavior on the harm of lottery betting. The responsible purchase belief also played a moderating role in the impact of improper lottery betting promotion on gambling addiction behavior, which could buffer the impact of improper lottery betting promotion on gambling addiction behavior and the impact of problem gambling behavior on the harm of lottery betting.ConclusionThe mediating model constructed in this study to some extent reveals the mechanism of the impact of improper promotion on the harm of sports betting, and provides theoretical support and practical guidance for preventing the risk of harm from sports betting.